A new proposal of utilizing intraoperative electron radiation therapy on the surface of liver to prevent postoperative liver metastasis of pancreatic cancer. (May 2019) - Dong, Yiting; Song, Zikuan; Luo, Yuling; Ma, Xuelei
Abstract: Pancreatic cancer is a lethal cancer with high rate of liver metastasis worldwide, whereas its treatment choices are limited to a large extent. The limitation of current therapeutic strategies calls for an effective approach which can lower the postoperative liver metastasis rate in order to improve the overall prognosis and survival rate. Comprehensively considering the basic knowledge and clinical practice of tumor treatment worldwide, we proposed three points of hypotheses. Basically, the existing evidences indicated that tumor cells shedding from pancreatic cancer localized in the marginal liver preferentially through the Portal vein. Then, the percentage depth dose distribution of electron radiation is consistent with the marginal distribution of liver metastasis from pancreatic cancer. Based on the characteristics of liver metastasis of pancreatic cancer and the percentage depth dose of electron radiation, we provide a new propose of preventing postoperative liver metastasis in a way of prophylactic intraoperative electron radiation therapy on the surface of liver. Intraoperative electron radiation is relatively easy to control radiation dose and treatment area under direct vision, effectively inhibiting the metastasis and growth of cancer cells and preventing further deterioration of pancreatic cancer patients' condition. Therefore, this hypothesis has an important clinical significance for postoperative rehabilitation and improvement of patients' survival.